2005
DOI: 10.1073/pnas.0500496102
|View full text |Cite
|
Sign up to set email alerts
|

DNA coiled coils

Abstract: We report the coiled-coil structure of DNA, which is generated by the dodecanucleotide d(ATATATATATAT). The structure has been determined by single-crystal x-ray crystallography. The molecules form duplexes with single-stranded overhangs, which associate with neighbor molecules and give rise to infinite double helices in a coiled-coil conformation, with staggered nicks in both strands. The coiled coils have six dodecamer duplexes per turn. Despite the presence of nicks, the structure is very rigid. Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
(31 reference statements)
4
20
1
Order By: Relevance
“…[2] The presence of continuous diffraction indicates screw disorder, with parallel orientation of the diffracting entities. Slight variations in the crystallization conditions resulted in crystals that show little screw disorder and Bragg spots that extend for up to 3 .…”
Section: Structure Of the Dna Coiled Coil Formed By D(cgatatatatat)mentioning
confidence: 99%
See 3 more Smart Citations
“…[2] The presence of continuous diffraction indicates screw disorder, with parallel orientation of the diffracting entities. Slight variations in the crystallization conditions resulted in crystals that show little screw disorder and Bragg spots that extend for up to 3 .…”
Section: Structure Of the Dna Coiled Coil Formed By D(cgatatatatat)mentioning
confidence: 99%
“…The crystals were practically isomorphous to those previously described. [2] We determined the 3.1 X-ray structure and found that this dodecamer forms a continuous coiled coil with Hoogsteen base pairs between A and T.…”
Section: Structure Of the Dna Coiled Coil Formed By D(cgatatatatat)mentioning
confidence: 99%
See 2 more Smart Citations
“…If the DNA molecules assume a minimum spherical volume, the 48 kbp and 300 bp fragments will have particle diameters of 57.25 nm and 11.6 nm, respectively [42].…”
Section: Experimental Samplesmentioning
confidence: 99%